Highly sensitive strain sensor and self-powered triboelectric nanogenerator using a fully physical crosslinked double-network conductive hydrogel. (15th December 2022) - Luo, Yuecong; Yu, Maolin; Zhang, Yutong; Wang, Yuanyuan; Long, Lan; Tan, Haihu; Li, Na; Xu, Lijian; Xu, Jianxiong
Abstract: Stretchable and conductive hydrogels have broad application prospects in various portable and wireless electronic devices and sensors. However, most hydrogels used to construct strain sensors and triboelectric nanogenerators (TENGs) suffer from poor mechanical properties and lack of adhesion till this day. To address these issues, fully physical crosslinked PVA/P(AM- co -AA)-Fe 3+ double-network hydrogel (DN gel) was prepared. The unique DN structure endows the hydrogels with excellent mechanical properties (2.1 MPa tensile stress, 6.5 MJ/m 3 toughness, 0.4 MPa elastic modulus) and the strong adhesion on various material surfaces. The DN gel as a strain sensor shows high sensitivity (GF = 2.3) and wide sensing range of 1–300%. In addition, the TENG based on PVA/P(AM- co -AA)-Fe 3+ (PP-TENG) with an area of 2 × 2 cm 2 exhibits attractive electrical output properties, including a maximum open-circuit voltage (VOC ) of 238 V, a short circuit current (ISC ) of 1.2 μA, and a short-circuit transferred charge (QSC ) of 37 nC at a fixed frequency of 2 Hz. Moreover, their applications in highly sensitive strain sensor to effectively distinguish complex human activities and transmit encrypted information, as well as self-powered TENG to power commercial light-emitting diodes and calculator are described. It is foreseen that the as-prepared stretchable and conductive hydrogels have great potential in wearable electronic devices, human-health care, and energy harvesting systems. Graphical Abstract: ga1 Highlights: PVA/P(AM- co -AA)-Fe 3+ showed high sensitivity, wide sensing range and strong adhesion on various material surfaces. The hydrogel-based strain sensor could distinguish complex human activities and transmit encrypted information. The TENG based on hydrogel could power small electronic devices.